Walchand Hirachand Doshi - Visual History of Business and Trade in India (2022)
Regarded as the 'Creative Genius' by the late President of India, Dr. APJ Abdul Kalam, Seth Walchand Hirachand Doshi is remembered as a visionary who laid down the foundation of industrialization in India. He is credited for his immense contributions to establishing ventures in the fields of civil engineering, aircraft manufacturing, maritime shipping, and automobile manufacturing, which were then nationalized by the government. He never had an interest in carrying out the traditional family business of the cotton trade and started his career as a railway contractor. He founded the Scindia Steam Navigation Company, establishing the first national shipping industry of India, which sailed its first ship SS Loyalty from Mumbai to London on April 5, 1919. Analyzing the role of ship-building in the infrastructure development of India, he took the initiative of building a shipyard in Vishakhapatnam in 1948. This shipyard was then nationalized by the government of India and was renamed Hindustan Shipyard Limited. Another major contribution by Seth Walchand was the setting-up of India's first aircraft manufacturing facility 'Hindustan Aircraft Limited', renamed HAL in the later period. Follower of nationalist leaders like Dadabhai Navroji, Justice M.G. Ranade, Rao Bahadur G.V. Joshi, and R.C. Dutt, Walchand always dreamt of shaping the future of India and gave all the efforts and dedication to bringing those dreams to reality.